Using the concept of spatial justice for a better understanding of contemporary metropolitan areas of South Africa - (:unkn) unknown (My University, 2017)
The paper applies the concept of spatial justice to a case study of urban South Africa, focusing on the Province of Gauteng. It argues that it is a matter of urgency to go beyond simply measuring inequalities and to work also on how they are perceived, and therefore on perceptions and representations of what is just and unjust. It is all the more urgent because, in South Africa as in most of the world’s major cities, inequalities are on the rise and the population’s cultural diversity isincreasing or is more apparent and is perceived differently from the past. This is done here in a non normative way, using diverse definitions of social justice and confronting them with the diverse dimensions of space (both theoretical and representations made by local agents). After examining the spatial system under apartheid in terms of justice and injustice, the paper looks into the post-apartheid situation in general and, lastly, using a local-scale case study concerning theEkurhuleni Municipality.
Keywords: African Research